(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Women's participation in politics has decreased in Nigeria and worldwide. Many academics are pretty worried about the trend. However, mounting evidence supports the claim that women are making strides in political representation in contemporary societies. This development is evident in the political arena of Edo state, Nigeria. As a result, the study aimed to investigate the attitudinal dimension of women in the state toward engaging in political activities. Five hundred and sixteen women from various locations in Edo state were selected at random to participate in the study. Respondents completed a self-report measure of attitude toward political engagement. 78.3% of respondents, with a mean difference of 0.98, exhibited a more favorable attitude toward political participation than 21.7% of their counterparts. It was concluded that attitude is a crucial component of the link between women and politics. It is proposed that women's political participation be encouraged.